Speech enhancement using discrete kalmanfilter algorithm - Shanmukha, J; S.Ramesh, K; Koteswar Rao, S (International Journal of Engineering and Technology, 2018)
Enhancement of speech deals with the noise reduction which is mostly essential in many applications like teleconferencing sys tem. The nearness of added substance foundation noise degenerate the discourse in correspondence condition. In the event that the commotion is developing slower than discourse which implies noise is more stationary than speech .Estimation of noise ends up noticeably s impler when delays happened in speech. In this work discrete Kalman channel calculation which gauges the inward condition of a direct powe r-ful framework.